The impact of childhood sexual, physical and emotional abuse and neglect on suicidal behavior and non-suicidal self-injury: A systematic review of meta-analyses - CHIA, Yuan Yu Alicia (Institutional Knowledge at Singapore Management University, 2025)
Self-injurious thoughts and behavior, encompassing suicidal ideation, attempts and non-suicidal self-injury, represent a critical global health concern. Amidst the multifaceted nature of these behaviors and the various underlying risk factors, childhood maltreatment emerges as significant risk factor. The current umbrella review synthesizes literature across diverse geographical regions including Africa, Asia & Pacific, Europe, Middle East, North America, Latin America and Oceania incorporating findings from 24 meta-analyses that cumulatively analyze 81 effect sizes. The review reveals a consistent association between various forms of childhood maltreatment and an increased risk of self-injurious thoughts and behaviors across different populations. Importantly, our findings show that childhood physical (Mdn OR = 2.52), emotional (Mdn OR = 2.75), and sexual abuse (Mdn OR = 2.56) have comparable impacts on such behaviors, highlighting the severity of all childhood abuse sub-types. Similarly, we also found that emotional neglect (Mdn OR = 1.89) has a similar impact as physical neglect (Mdn OR = 1.57) in predicting self-injurious thoughts and behavior. Our findings underscore that all forms of childhood maltreatment pose comparable significant risks and highlight the necessity for comprehensive, trauma-informed interventions to mitigate the risk of self-injurious thoughts and behaviors.